Protoplast-mediated transformation of Madurella mycetomatis using hygromycin resistance as a selection marker. - Saskia du Pré; Mickey Konings; Dorenda J A Schoorl; Ahmed H Fahal; Mark Arentshorst; Arthur F J Ram; Wendy W J van de Sande (Public Library of Science (PLoS), 2024)
Madurella mycetomatis is the main cause of mycetoma, a chronic granulomatous infection for which currently no adequate therapy is available. To improve therapy, more knowledge on a molecular level is required to understand how M. mycetomatis is able to cause this disease. However, the genetic toolbox for M. mycetomatis is limited. To date, no method is available to genetically modify M. mycetomatis. In this paper, a protoplast-mediated transformation protocol was successfully developed for this fungal species, using hygromycin as a selection marker. Furthermore, using this method, a cytoplasmic-GFP-expressing M. mycetomatis strain was created. The reported methodology will be invaluable to explore the pathogenicity of M. mycetomatis and to develop reporter strains which can be useful in drug discovery as well as in genetic studies.